Synthesis and Evaluation of Gelatin-Folate for CNS Targeting using Phenytoin Sodium Nanoparticles - Punitha, D. Antony Deva (My University, 2016)
According to World Health Organization (WHO), neurological disorders and their prevalence are at rise, and the world-wide prevalence of neurological disorders by 2030 will be 1100 million. Central nervous system (CNS) targeting deserves much attention because of the conglomeration and high prevalence of CNS disorders. In clinical development, CNS-acting drugs have the poorest success rate. Development of more than 98% of such candidates had to be discontinued because of poor permeability across the blood–brain barrier (BBB), and this presents a major problem to the pharmaceutical industry. Perhaps, the only object which holds those advancements back is BBB, and is called for its better understanding for the better treatment of CNS disorders. Though the BBB is greeted for its neuroprotection, it symbolizes a formidable obstacle for both macro to micro, and hydrophilic to lipophilic molecules in CNS targeting. Multiple transporters are expressed in the brain microvessel endothelial cells (BMEC) that line cerebral capillaries of the BBB and they influence the BBB permeability of molecules that are their substrates. The BMEC has been equipped with three different specialized mechanisms of solute transfer. Briefly, blood-to-brain influx transport system, Brain-to-blood efflux transport system and Drug efflux pump. Drug efflux pump prevents entry of xenobiotics into the brain by pumping them out. Adenosine triphosphate (ATP)-binding cassette (ABC) transporter is a chief member of efflux pump transporters. Prevention of intercalation and diffusion of xenobiotics into cell membranes is carried out by these transporters as protective means. They are transmembrane protein transporters situated in BBB as well as other parts of the body. ABC efflux transporters have made drug permeation across the BBB more complex. However, amidst the presence of effective efflux transporters, BBB transportation of endogenous substrates and even therapeutics that mimic endogenous substrates occurs with no restrictions. Transportation of drugs that are not recognized by receptor on their own accord could be achieved through chimeric peptide technology. Herein, a nontransportable drug is conjugated to a BBB transport vector/ ligand which has its receptor expression in the BBB, and undergoes transcytosis. The transport vectors could be conjugated either directly to the drug compounds or to the surface of particulate colloidal carriers viz. nanoparticles, liposomes, etc. through covalent or non-covalent linkage. Folic acid (pteroylglutamic acid), also known as Vitamin B9 Among the CNS disorders, the prevalence of epilepsy is as high as other abreast CNS disorders. The epilepsies are common and have frequently devastating influences, affecting approximately 2.5 million people in the United States alone and about 4 % of individuals (50 million) over their lifetime worldwide. More than 40 distinct forms of epilepsy have been identified. , and its double-reduced form tetrahydrofolate are cofactors of several enzymes and a notable endogenous substrate. Further, its receptor has wildly been expressed in the cells of brain and CP. Folate is relatively easy to ligate to any therapeutics, and retains its ability to bind to its receptor with normal affinity when attached via its γ-carboxylate, and thereby enter receptor-bearing cell by endocytosis. People with epilepsy are well known to be at increased risk of sudden death. Phenytoin Sodium (DPH) is an excellent anticonvulsant and because of its putative mechanisms of action, it masters three different conditions like Grandmal, Partial & status epileptics. However, it is a good candidate of P-glycoprotein (P-gp), Mrp1, Mrp2, and BCRP. Recent studies have suggested that overexpression of Pglycoprotein in the hippocampal region affects brain uptake of phenytoin in epileptic rats and causes a decrease of local DPH levels in the rat brain. Even, it has been observed that expression of multidrug resistance–associated proteins MRP1 and MRP2 and breast cancer–resistance protein (BCRP) was upregulated shortly after status epilepticus, during the Latent Period, and in Chronic Epileptic Rats, and affects distribution of DPH in the brain. Gelatin is a natural, inexpensive, low immunogenic, non-toxic, and good biodegradable macromolecule. The US Food and Drug Administration (FDA) classified gelatin as a “Generally Recognized as Safe” excipient. As a protein-based product, gelatin possesses several functional groups which are available for covalent modifications for drug or ligand binding. And useful in targeted drug delivery. In this context, FA was attached to gelatin through amide bond, between γ -carboxyl group of FA and primary amino groups of gelatin, using EDC chemistry. Gelatin-folate was precipitated using acetone. It was characterized by using modern analytical techniques such as IR, NMR (1H NMR, 13C NMR COSY and HSQC) for chemical characterization and DSC and XRD for solid state characterization and SEM for morphological characterization Gelatin nanoparticles were formulated by two step desolvation method and the formulated nanoparticles were optimized for formulation variables such as percentage of polymer, degree of cross-linking and duration of crosslinking. Further, nanoparticles were studied for particle size, PDI, zeta potential, total drug content and drug loading (%DL), in vitro release and drug release mechanism. Formulation GT3 showed better loading efficiency and release profile. According to the composition of GT3, gelatinfolate Nanoparticles (GF1) were formulated and the above characterizations were done. Further, nanoparticles were studied by DSC and XRD for solid state characterization and SEM for morphological characterization. Residual solvents present in synthesized Gelatin folate and nanoparticles formulation GT3 and GF1 were recorded on Gas chromatography head space using flame-ionization detector. All the tested compounds were free from residual solvents. Pharmacodynamics (in vivo) was studied through Maximal electroshock induced seizure model (corneal electroshock method) in rat using simple phenytoin solution (DPH Soln), its gelatin nanoparticles (DPH-NP-FA), and gelatin-folate nanoparticles (DPH-NP-FA). All the formulations showed significant decrease in duration of hind limb extension as compared to vehicle treated group. DPH-NP-FA significantly potentiated the anticonvulsant action of phenytoin by reducing its ED50 value from 12 mg/kg to 7 mg/kg against Maximal electroshock induced seizure. Pharmacokinetic profiles were studied by administration of single dose of three different phenytoin formulation viz. DPH Soln, DPH-NP, and DPH-NP-FA, equivalent to 30mg/kg of phenytoin per oral in rats and comparing their plasma pharmacokinetics to brain neuropharmacokinetics. The brain Cmax and AUC values of phenytoin were substantially lower to those in plasma and the brain/plasma AUC ratio was 0.1. After DPH-NP-FA administration, the brain Cmax and AUC were increased from 1.2 ±0.33 to 4.1±0.26 μmol/l and 3.5 ±0.12 to 14.5±0.2 h*μmol/l, respectively and the brain/plasma ratio was improved from 0.1 to 0.4, whereas the ratio was 0.1 and 0.16 after DPH soln, DPH-NP administration, respectively. The order of the ratio suggests that equilibrium between the blood and brain compartments was not observed for all the 3 formulations at the evaluated dose. In this study, folic acid was covalently attached to gelatin, and nanoparticles of gelatinfolate using DPH were prepared. The formulated nanoparticles were studied for drug loading (%DL), in vitro release and drug release mechanism along with other physiochemical properties. Pharmacodynamic and Pharmacokinetic profiles of formulated nanoparticles were studied. From the above study, it can be concluded that gelatin-folate nanoparticles showed better pharmacokinetics profile in both compartment
Keywords: Synthesis; Evaluation of Gelatin-Folate; Targeting using Phenytoin Sodium Nanoparticles